Path coefficient analysis of haemato-biochemical traits to explore the heat stress in native Khadia chicken population of northern Odisha, India - A SAHOO; G D NAYAK; B C DAS; K K SARDAR (Indian Journal of Animal Sciences, 2022)
The aim of the present study was to evaluate the haemato-biochemical parameters of native Khadia chicken reared under backyard poultry production system. Data were collected from 280 Khadia chicken population. The haemato-biochemical parameters were altered significantly due to heat stress. The stress related traits, viz. heart rate (447.68Â±4.50 beat/min) and cloacal temperature (46.32Â±0.12) were recorded. The correlation between heart rate and AST was 0.76 and the correlation with other haemato-biochemical parameters was also significant under stressful conditions. Similarly, cloacal temperature also significantly correlated with haemato-biochemical parameters under thermal stress. The path coefficient analysis was executed to identify the direct effect of AST on heart rate and cloacal temperature which were 0.57 and 0.46, respectively. The multiple regression analysis showed AST is the central factor contributing to variation in stress related traits which can be used as a selection tool for selection at early stage of birds for thermal tolerance.